Sexual dysfunctions in psoriatic patients - Nowowiejska, Julia; Karny, Agata; Nesterowicz, Miłosz; Purpurowicz, Piotr; Baran, Anna; Kaminski, Tomasz W.; Purpurowicz, Zbigniew; Flisiak, Iwona (Frontiers in Public Health, 2024)
Psoriasis is one the most common skin diseases associated with a great decrease in the quality of patients' lives. We aimed to study sexual dysfunctions in psoriatic patients using the Female Sexual Function Index (FSFI) for women and the International Index of Erectile Function (IIEF) for men via an anonymous online survey. The study included 80 psoriatic patients and 75 controls without dermatoses. There was a downward trend in the total IIEF score in psoriatic men compared to controls. 58% of male patients and 76% of controls had a normal IIEF score. There was no significant difference in IIEF between patients treated and not with systemic agents. 62% of female patients had a decreased FSFI score, whereas in the control group, the majority of subjects (54%) had a normal FSFI score. There was no significant difference between FSFI score between patients and controls. Female patients treated with systemic antipsoriatic agents had significantly worse lubrication, satisfaction with sexual life, and pain. Our study has shown that the majority of questioned female psoriatic patients had sexual dysfunction according to FSFI, particularly they had worse satisfaction with sexual life and less sexual desire compared to women without psoriasis. The majority of male patients did not have sexual dysfunction according to IIEF, however, they had significantly worse overall satisfaction with sexual life and confidence to keep an erection. Systemic antipsoriatic treatment does not probably influence sexual dysfunctions in men but it does in women although we were not able to assess the severity or resolution of lesions after those treatments. However embarrassing, psoriatic patients should be questioned about their sexual lives by dermatologists, and more studies are needed to explore this matter.